Case-studies in physiology: The exercise pressor response to indoor rock climbing - Callender, N. A.; Hart, P. W.; Ramchandani, G. M.; Chaggar, P. S. (Journal of Applied Physiology, 2020)
Introduction: This paper assessed the blood pressure, heart rate, and mouth-pressure responses to indoor rock climbing (bouldering) and associated training exercises. Case Presentation: Six well-trained male rock climbers (mean ± SD age = 27.7 ± 4.7 y; stature = 177.7 ± 7.3 cm; mass = 69.8 ± 12.1 kg) completed two boulder problems (6b and 7a+ on the Fontainebleau Scale) and three typical training exercises (Maximum voluntary contraction [MVC] isometric pull-up, 80% MVC pull-ups to fatigue, campus-board to fatigue). Blood pressure and heart rate were measured via an indwelling femoral arterial catheter, and mouth pressure via a mouthpiece manometer. Bouldering evoked a peak systolic pressure of 200 ± 17 mmHg (44 ± 21% increase from baseline), diastolic pressure of 142 ± 26 mmHg (70 ± 32% increase), mean arterial pressure of 163 ± 18 mmHg (56 ± 25% increase), and heart rate of 157 ± 20 b/min (81 ± 30% increase). The highest systolic pressure was observed during the campus-board exercise (218 ± 33 mmHg), although individual values as high as 273/189 mmHg were recorded. Peak mouth pressure during climbing was 31 ± 46 mmHg, and this increased independent of climb difficulty. Conclusions. Indoor rock climbing and associated exercises evoke a substantial pressor response, resulting in high blood pressures that may exceed those observed during other resistance exercises. These findings may inform risk stratification for climbers.